2017
DOI: 10.1111/trf.14372
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative screening and intervention for mild anemia with low iron stores in elective hip and knee arthroplasty

Abstract: BACKGROUND Preoperative anemia in patients undergoing elective hip and knee arthroplasty is associated with increased postoperative morbidity and mortality, red blood cell (RBC) transfusion, and length of stay (LOS). The aim of this study was to assess the effect of optimizing hemoglobin (Hb) levels before elective primary hip and knee arthroplasty. STUDY DESIGN AND METHODS This is a prospective comparative cohort study of patients who underwent elective hip and knee arthroplasty before (control) and after (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 27 publications
0
41
0
3
Order By: Relevance
“…Preoperative identification and treatment of patients with anemia is considered one of the pillars of Patient Blood Management . Preoperative anemia has been identified as a preventable risk factor for perioperative transfusion, and preoperative hemoglobin optimization through iron supplementation has been shown to significantly reduce the intraoperative nadir for hemoglobin and reduce the need for perioperative transfusion in adults . Recent pediatric studies suggest a strong relationship between preoperative anemia, transfusion, and outcomes in both neonates and older children undergoing non‐cardiac surgery.…”
mentioning
confidence: 99%
“…Preoperative identification and treatment of patients with anemia is considered one of the pillars of Patient Blood Management . Preoperative anemia has been identified as a preventable risk factor for perioperative transfusion, and preoperative hemoglobin optimization through iron supplementation has been shown to significantly reduce the intraoperative nadir for hemoglobin and reduce the need for perioperative transfusion in adults . Recent pediatric studies suggest a strong relationship between preoperative anemia, transfusion, and outcomes in both neonates and older children undergoing non‐cardiac surgery.…”
mentioning
confidence: 99%
“…Successful implementation of preoperative anaemia optimisation for elective hip and knee replacement patients has been achieved and positive results reported from at least one NHS Trusts in England. (28) This work showed that a relatively straightforward clinical pathway including the use of oral and/or IV iron resulted in significant reductions in the number of patients transfused (6 v 4.1% p = 0.005), length of hospital stay (3.9 v 3.6 days p = 0.017), critical care admissions (1.27 v 0.55% p = 0.03) and hospital readmissions (4.5% v 3.0% p = 0.02). This was found to be cost effective, resulting in savings of £162.46 per patient screened, or £406,000 for a Trust performing 2500 primary THR or TKRs per annum.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Hb concentrations also prevent transfusion-related complications 19. Health economic analysis reveals significant savings from preoperative anaemia screening and management 2. The benefits of treating anaemia may not purely reflect increased Hb concentrations, as iron is important for cellular processes such as oxygen transport and cellular immunity 20…”
Section: Preoperativementioning
confidence: 99%
“…A study of arthroplasty surgeons in the USA revealed transfusion rates ranging from 3.8% to 63.8% for primary TKA,87 rising to 84% for bilateral TKA 88. Studies in the UK reported transfusion rates of 2.7% for primary TKA2 and 29.1% for revision TKA 4…”
Section: Postoperativementioning
confidence: 99%
See 1 more Smart Citation